The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0310057x1304100407
|View full text |Cite
|
Sign up to set email alerts
|

Epidural versus Continuous Transversus Abdominis Plane Catheter Technique for Postoperative Analgesia after Abdominal Surgery

Abstract: Transversus abdominis plane block is an effective postoperative analgesic technique after abdominal surgery, but no study has compared continuous transversus abdominis plane block with continuous epidural analgesia.We designed a randomised controlled trial comparing these techniques for major abdominal surgery. Patients in the epidural group received a bolus of 8 to 15 ml of ropivacaine 0.2% and an infusion of 5 to 15 ml/hour and the transversus abdominis plane block group a bolus dose of 20 ml of ropivacaine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 24 publications
2
65
0
Order By: Relevance
“…No differences were found in regards to pain scores, either in the immediate postoperative period or in surgical wards. Furthermore, total fentanyl requirement and satisfaction scores were similar between both groups 56 after multivariate analysis 57 . However, rectus sheath catheters with levobupivicaine bolus infusions (20mL of 0.25% every 6h) have been described in RC and appear to contribute to a decreased LOS (17d to 10.8d) as part of a multi-modal anesthesia plan 58 .…”
Section: Postoperative Pain Controlmentioning
confidence: 75%
“…No differences were found in regards to pain scores, either in the immediate postoperative period or in surgical wards. Furthermore, total fentanyl requirement and satisfaction scores were similar between both groups 56 after multivariate analysis 57 . However, rectus sheath catheters with levobupivicaine bolus infusions (20mL of 0.25% every 6h) have been described in RC and appear to contribute to a decreased LOS (17d to 10.8d) as part of a multi-modal anesthesia plan 58 .…”
Section: Postoperative Pain Controlmentioning
confidence: 75%
“…10,15,16,18,21 Of these trials, only 1 trial 10 demonstrated a significant analgesic benefit via improved patient satisfaction scores.…”
Section: Thoracic Epidural Analgesia Versus Tap Cathetersmentioning
confidence: 99%
“…Four trials 15,20-22 used boluses at 8-hourly intervals. Seven other trials 10,[16][17][18][19]23,25 administered local anesthetic by continuous infusion, ranging from 4 to 10 mL/h through each catheter.…”
Section: Local Anesthetic Administrationmentioning
confidence: 99%
See 2 more Smart Citations